Theoretical and methodological elements of a community strategy for the prevention of the consumption of psychoactive substances (PAS) in young university students - Chaves-Cerón, Margarita; Yépez-Chamorro, María Clara (Universidad y Salud, 2023)
Introduction: The use of psychoactive substances in the university environment has been a public health problem that must be addressed to strengthen the integral development of students. Objetive: The purpose of the study carried out was to inquire about theoretical and methodological elements that allow to prevent, control and mitigate the problem within the University. Materials and methods: The research process was developed under the logic of the qualitative paradigm, with an ethnographic design, in the construction of the methodological strategy, Action research techniques were used. Results: The strategy was based on factors related to the structural and intermediate determinants of health that were the guides in the construction of activities related to community psychology, promotion, communication and health education, as well as actions proposed by the Health authorities in Colombia. Conclusions: The study made it possible to show that there are points of confluence between the different perspectives where it was recognized that aspects such as norms and laws, family environment, social bond, race, ethnic group and customs of society, are factors of social determinants that can influence a young person to consume psychoactive substances within the University.